Evaluation of ompA and pgtE genes in determining pathogenicity in Salmonella enterica serovar Enteritidis. (December 2016) - Zhou, Y.; Zhou, J.; Wang, D.; Gao, Q.; Mu, X.; Gao, S.; Liu, X.
Highlights: Mutants of ompA and pgtE were constructed in a virulent S. Enteritidis isolate. The phenotype of mutants was evaluated in in vivo and in vitro infection assays. OmpA and pgtE genes played important roles in S. Enteritidis infection in chickens. Abstract: Salmonella enterica subsp . enterica serovar Enteritidis ( S . Enteritidis) is a major causative agent of gastroenteritis in humans. This important food-borne pathogen also colonises the intestinal tracts of poultry and can spread systemically, especially in chickens. To identify the S. Enteritidis virulence genes involved in infection and colonisation of chickens, chromosomal deletion mutants of the ompA and pgtE genes, which encode essential components of omptins, were constructed. There were no significant differences between the wild-type and ompA and pgtE mutants in a series of in vitro assays, including an intracellular survival assay, survival in specific-pathogen-free (SPF) chicken serum, and in vitro competition assays. In contrast, in vivo competition assays revealed that ompA and pgtE mutants underwent attenuated growth in liver, cardiac blood, spleen, lung, and kidney compared to a wild-type strain (CVCC3378). When tested in SPF chickens, ompA or pgtE gene inactivation substantially reduced organ colonisation and delayed systemic infection compared with the wild-type strain. Colonisation was restored in S. Enteritidis mutants by reintroduction of the whole ompA or pgtE gene with the native promoters. The results of this study demonstrate that ompA and pgtE play an important role in the pathogenesis of S. Enteritidis and its ability to infect chickens.